Analisis Persepsi Mahasiswa Terhadap Ancaman Phishing Sebagai Tindak Pidana Perbankan (Studi Kasus Pada Mahasiswa Perbankan Syariah Unisnu Jepara) - Nevy dia sanadyanta; Sheftiyani fazrina; Rizka laili amelia; Sri wulandari; Faridlotun Ni’mah; Wahidullah (IAI Nasional Laa Roiba Bogor, 2025)
This study analyzes the perception of students of the Islamic Banking Study Program of Nahdlatul Ulama Jepara Islamic University towards the threat of phishing as a banking crime. In the digital era, students have the potential to become agents of change in creating a safe Islamic banking ecosystem, but low digital literacy and education about data security make them vulnerable to online fraud. This study aims to explore students' understanding of the mechanism of phishing attacks, their level of awareness of cyber risks, and the factors that influence their perceptions and responses. The method used is qualitative with literature studies and interviews to obtain in-depth data. The results of the study show that the level of student understanding varies, some already understand this threat well, while others are still less familiar. Education from the campus is needed to increase students' awareness and understanding of the dangers of phishing, so that it can strengthen digital literacy and personal data protection among them.